PENGARUH INTERVENSI GIZI MULTIKOMPONEN PADA GURU, ORANG TUA DAN SISWA SEKOLAH DASAR TERHADAP PENGETAHUAN, SIKAP DAN KETERSEDIAAN BUAH SAYUR DI RUMAH[Effect of Multicomponent Nutrition Intervention on Teachers, Parents, and Elementary School Students towards Knowledge, Attitude and Availability of Fruits and Vegetables at Home] - Nila Reswari Haryana; Lilik Kustiyah; Siti Madanijah (Universitas Airlangga, 2019)
Consumption of fruits and vegetables in children is strongly influenced by several factors, such as lack of knowledge and attitude. However, eating behavior in children is also caused by the behavior of teachers and parents in eating fruits and vegetables which also influenced by knowledge and attitude. Therefore the purpose of this study was to analyze the effect of multicomponent nutrition intervention on teachers, parents, and elementary school students towards knowledge, attitude, and availability of fruits and vegetables at home. The design of this study was quasi-experimental. The intervention given to the subjects were nutritional education to three groups and giving fruits and vegetables in Nganjuk District, East Java in February-May 2017. Subjects were 10 teachers, 31 parents and 31 students. The data were analyzed by Friedman-test. After intervention, there was a significant increase of knowledge and attitude in teachers and (p=0.009) in students (p=0.000) and parents (p=0.000). Fruit availability at home increased significantly (p<0.05), on the other hand, vegetables availability not significantly increased. Involving teachers and parents were important in nutrition intervention for children. Increasing the availability of fruits and vegetables at home can increase children fruit consumption.